PEMBAGIAN PEMBANGKITAN SISTEM PEMBANGKIT TERMAL PADA KONDISI BEBAN YANG BERUBAH TERHADAP WAKTU MENGGUNAKAN QUADRATIC PROGRAMMING - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
Power plant distribution by considering load change towards time is the development of conventional power distribution because it calculates the ramp rate unitr parameter of power plant. Power distribution of thermal power plant under the load condition that change toward time is used to determine the optimum generation schedule so that it can fulfill the load demand with minimum operational cost when sharing the limitation of system and operation throughout the whole period of generation. Spinning reserve is also considered in power plant distribution, since spinning reserve is used for maintaining the system’s constraint of each operations. In this case, if one unit of power plant is failed, there must be any capacity that could supply the power from another unit to accomplish such condition that happens within a period. This research uses quadratic programming to accomplish power distribution that calculates load change toward time, thus solve power distribution without trespassing the ramp rate parameter and spinning reserve which has been specified. Three unit of power plants were used in this research with short - term load demand and specified ramp rate . From the analysis of results, it can be seen that quadratic programming is not violate constrain ramp rate of power plant, whilst conventional method can not do the calculation of generation with a ramp rate constraint. The result analysis also shows that generation cost using quadratic programming is cheaper ($46659,49) compared to that of conventional method ($47064,01).